Nanocomposite Kaolin/TiO2 as a Possible Functional Filler in Automotive Brake Pads. (21st November 2018) - Dědková, Kateřina; Morbach, Marcus; Výravský, Jakub; Kutláková, Kateřina Mamulová; Čabanová, Kristina; Vaculík, Miroslav; Kukutschová, Jana
Abstract : An automotive friction brake pad is a complex system consisting of several components with unique and balanced properties related to operation conditions. There are efforts to develop brake pads with longer lifetime and better friction performance and wear properties. Those properties are related to composition of the pads, and therefore, new materials are being evolved. Tuning the friction and wear properties can be achieved with the selection of a functional filler and optimizing its amount in a formulation of friction brake pad. Laboratory-developed and laboratory-prepared nanocomposite material kaolin/TiO2 (KATI) has been introduced to formulation of the commercially available automotive low-steel brake pad. Kaolin was utilized as a matrix for anchoring TiO2 nanoparticles. New unused pads and pads after AK master, a standard dynamometer testing procedure of friction performance, were investigated using light and scanning electron microscopy providing information on the structure and its changes after the friction processes. Moreover, MTK wear test was used to compare wear rate of the newly developed pad with the reference low-steel pad. Improved durability of the brake pad formulation has been observed together with sufficient friction performance. Microscopic analysis shown homogenous distribution of the KATI nanocomposite in the friction layer. From the obtained results, it can be assumed that the new formulation is promising regarding to the life cycle of the pads and reduction of wear rate and thus potential production of wear particulate emissions.